Three Strategic Pillars : Finnish University Libraries' Network Fuelling Open Science and Access to Research-Based Information - Lehto, Anne; Abrahamsson-Sipponen, Minna; Harju, Tommi; Parikka, Susanna; Södergård, Pia (International Association of University Libraries, 2021)
In the fast-developing landscape of open science, university libraries need to constantly keep up to date in order to provide expert services that meet the current and future needs of researchers, students, and anyone in need of research-based information. Joint actions are needed both nationally and internationally. The COVID-19 pandemic has shown that open science currently only gives partial access to research information. A significant part of the information resources are behind paywalls, and as library premises have been closed for the public walk-in access, the information resources have not been accessible to a wider audience.
Keywords: kirjastot; yliopistokirjastot; yhteistyö; tieteelliset kirjastot; kirjastopalvelut; kehittäminen; COVID-19; avoin tiede